Fruits of the forest: Human stable isotope ecology and rainforest adaptations in Late Pleistocene and Holocene (∼36 to 3 ka) Sri Lanka. Issue 106 (May 2017) - Roberts, Patrick; Perera, Nimal; Wedage, Oshan; Deraniyagala, Siran; Perera, Jude; Eregama, Saman; Petraglia, Michael D.; Lee-Thorp, Julia A.
Abstract: Sri Lanka has yielded some of the earliest dated fossil evidence for Homo sapiens ( ∼ 38-35, 000 cal. years BP [calibrated years before present]) in South Asia, within a region that is today covered by tropical rainforest. Archaeozoological and archaeobotanical evidence indicates that these hunter-gatherers exploited tropical forest resources, yet the contribution of these resources to their overall subsistence strategies has, as in other Late Pleistocene rainforest settings, remained relatively unexplored. We build on previous work in this tropical region by applying both bulk and sequential stable carbon and oxygen isotope analysis to human and faunal tooth enamel from the sites of Batadomba-lena, Fa Hien-lena, and Balangoda Kuragala. Tooth enamel preservation was assessed by means of Fourier Transform Infrared Spectroscopy. We use these data to produce a detailed stable isotope ecology for Late Pleistocene–Holocene foragers in Sri Lanka from ∼ 36-29, 000 to 3000 cal. years BP, allowing us to test the degree of human tropical forest resource reliance over a considerable time period. Given that non-human primates dominate the mammalian assemblages at these sites, we also focus on the stable isotope composition of three monkey species in order to study their ecological preferences and, indirectly, human hunting strategies. The results confirm a strong human reliance on tropical forest resources from ∼ 36-29, 000 cal. years BP until the Iron Age ∼ 3 cal. years BP, while sequential tooth data show that forest resources were exploited year-round. This strategy was maintained through periods of evident environmental change at the Last Glacial Maximum and upon the arrival of agriculture. Long-term tropical forest reliance was supported by the specialised capture of non-human primates, although the isotopic data revealed no evidence for niche distinction between the hunted species. We conclude that humans rapidly developed a specialisation in the exploitation of South Asia's tropical forests following their arrival in this region.